The Design and Development of a Survey Instrument to Measure Factors that Influence Choice Goals of Forensic Science Majors - Steinmetz, Stacey (My University, 2016)
Colleges and universities are encouraged to strengthen forensic science programs to combat that shortage of highly educated and trained forensic scientists entering the field. To meet these demands and expectations, post-secondary institutions would benefit by knowing which students are selecting this career path and why. The purpose of this study was to design a reliable and valid survey instrument that measures factors which may influence students' decisions to major in forensic science. The survey instrument contained four sections and was administered to 106 college students enrolled in an introductory forensic science course. In section one, students were found to have high self-efficacy in tasks and skills associated with the field. In section two, students possessed high outcome expectations for their futures if pursuing a degree in forensics. In section three, students had average realistic, investigative, and enterprising interests, above average artistic and conventional interests, and below average social interests. In section four, students identified a variety of contextual supports and barriers that affected their decisions to major in forensic science. The sections measuring self-efficacy, outcome expectations, and interests were found to be reliable and valid with minor or no modifications, while the section measuring contextual supports and barriers was not. A new section measuring contextual supports and barriers was designed and provided. Conducting additional pilot studies to confirm the reliability and validity within all sections is recommended.
Keywords: forensic science; Social Cognitive Career Theory; survey development